2010
DOI: 10.1177/0363546510388386
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of the Donor Knee After Autologous Osteochondral Transplantation for Capitellar Osteochondritis Dissecans

Abstract: A time lag was evident in recovery between postoperative symptoms and muscle power at 3 months. However, harvesting osteochondral grafts did not exert adverse effects on donor knee function in young athletes at 2 years after undergoing osteochondral autograft transplantation for capitellar osteochondritis dissecans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…All but one patient had an excellent result based on the Mayo elbow performance score. Furthermore, greater than half of the patients returned to previous levels of sport or higher [49]. Microfracture and retrograde drilling remain good options with consistent, reproducible results in shallow OCD lesions without lateral column involvement.…”
Section: Microfracture/retrograde Drillingmentioning
confidence: 86%
“…All but one patient had an excellent result based on the Mayo elbow performance score. Furthermore, greater than half of the patients returned to previous levels of sport or higher [49]. Microfracture and retrograde drilling remain good options with consistent, reproducible results in shallow OCD lesions without lateral column involvement.…”
Section: Microfracture/retrograde Drillingmentioning
confidence: 86%
“…In their case report, the patient was able to return to painless normal function, lacking only 20 of internal rotation at both 0 and 90 of abduction as compared with the opposite extremity. As stated previously, our preference is to harvest from the knee at the distal lateral trochlea just proximal to the sulcus terminalis using a mini-open approach, which has been shown to cause minimal morbidity 6 and is easily reproducible. Garretson et al 7 showed that the distal lateral trochlea has the lowest contact pressure among the lateral knee sites and is a desired location of autograft harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Garretson et al 7 showed that the distal lateral trochlea has the lowest contact pressure among the lateral knee sites and is a desired location of autograft harvest. In a study by Nishimura et al, 6 12 patients underwent osteochondral autograft transport for severe osteochondritis dissecans of the humeral capitellum. Each patient received donor autograft plugs from the ipsilateral knee at the sulcus terminalis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations